PENGARUH MODEL PEMBELAJARAN RADEC (READ, ANSWER, DISCUSS, EVALUATE, CREATE) TERHADAP KETERAMPILAN BERPIKIR TINGKAT TINGGI SISWA KELAS 6 SD AL HUSNA KOTA TANGERANG - Azzahra Dhiya Afiyah; Romi Ramdon Ginanjar; Warsito (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study investigated how the Read, Answer, Discuss, Evaluate, and Create (RADEC) learning model affects sixth-grade students’ higher-order thinking skills at SD Al Husna in Tangerang City. Using a quantitative method, The study used a quasi-experimental design with a control group that was established pre-test–post-test. Through a saturated sampling approach, every student in the sixth grade was included as part of the study. The experimental group, Class VI A with 18 students, received instruction through the RADEC model, whereas the control group, Class VI B with 23 students, was taught using conventional methods. Students’ higher-order thinking skills were evaluated through a written assessment comprising nine essay questions. A t-test was used to analyze the data. As indicated by a t-value of 0.994, which was less than the t-table value of 2.022, the pre-test results showed no discernible variations in the starting abilities of the two groups. In contrast, post-test results indicated a t-value of 2.617, surpassing the t-table value and demonstrating that the experimental group's progress was noticeably higher than the control group's. These results suggest that the RADEC learning model offers more advantages than traditional teaching in fostering critical, analytical, and creative thinking. As such, RADEC presents itself as an effective instructional substitute for enhancing higher-order cognitive abilities in elementary education, encouraging students to become more reflective and self-directed learners.